Cultural Heritage of Pakistan: Conservation Problems and Techniques for its Protection - Saeed, T. (The Nucleus, 2022)
Pakistan is one of the fortunate countries of the world which possesses earliest socio-political history that goes back to Paleolithic. Its continuation has been expected to the significant period of about 2 million old from today. The areas of this Paleolithic culture have been found in the Potohar (or Pothohar) plateau, the area in and around district Rawalpindi, Punjab province of Pakistan, predictable to have been the most primitive habitat of the human species. This region in fact had played an active role in the evolution of human history since remote antiquity. This is the land where a number of ancient civilizations, cultures, religions art and architecture developed from prehistoric period to the Muslim period including British colonial era. The historical period monuments are well known ranging from the caravan serais (Inn) and baolis (step well) along the ancient routes, to historical forts, religious and secular buildings of Hindu, Muslim and Sikh periods, rock shelters, pre and historic mounds, graveyards and sacred ponds in the region. During the British Colonial rule “Archaeological Survey of India” was formed in the year 1860 for archaeological researches. At the time of independence of Pakistan, new department with the name “Department of Archaeology & Museums” (DOAM) was created to perform same functions and obligations. Since its inception the Department of Archaeology and Museums, Government of Pakistan has been performing its activities until 2011 when in sequel of 18th constitutional Amendments, all sites and monuments along with technical and financial resources were transferred to respective provinces.